STUDI LITERATUR: MOBILISASI DINI TERHADAP PENURUNAN SKALA NYERI PADA PASIEN POST LAPARATOMI - Virdian Cristiyaningsih; Okti Sri Purwanti (Jurnal Kesehatan, 2023)
Post-laparotomy patients will complain of pain, which if not treated immediately will cause discomfort that hinders treatment, as well as patient movement. Interventions that can be done to reduce pain can use pharmacological techniques with drugs or without drugs by doing relaxation and distraction (activity or early mobilization). This literature study aims to explore the effect of early mobilization on reducing the pain scale in post-laparotomy patients. The method of searching for articles in this literature study is through 2 databases (Google scholar, Pubmed). With keywords in English, namely laparotomy, mobilization, pain, and Indonesian, namely pain, laparotomy, early mobilization. A total of 6 studies met the inclusion criteria, consisting of 2 quasi-experimental methods, 1 case study article, 1 true experimental method with control group, and 2 cohort study methods. Early mobilization is an exercise that can reduce pain in post-laparotomy patients. Further research needs to be done to determine the frequency of movements to optimize patient mobilization. Patients must be trained to mobilize immediately, the first movements that can be done are bending the arms or hands, lifting the heels, rotating the ankles, training to tighten the calf muscles, flexion and movement of the feet. After 6-10 hours postoperatively the client can change positions lying on his left and right sides and 24 hours after surgery train the client to learn a sitting position. The movements that are intervened in the client provide energy to improve the patient's functional ability, the sooner the client mobilizes after surgery, the better the client's physical recovery will affect the client's recovery.